Contribution of Heat and Dust to Evergreen Elements I.E. Love and Culture: Exploring the Dislocation of Love and Culture in the Novel (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The treatment of lovein its purest form has been overshadowed by the sensational acts carried out bythe two British women. What makes this issue mostly striking is that RuthJhabvala, in place of focusing her attention on the relationship betweenDouglas and Olivia, or Inder La1 and Ritu, shifts it on the Nawab-Olivia andNarrator-Inder affairs, and thus making it clearly an issue dislocated from theusual location. This is exactly where the novel gets extra mileage. Otherwisethe novel has all the interests of a sensational work